2018
DOI: 10.3324/haematol.2017.183525
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of IDH1/2 mutant allele burden during follow-up in acute myeloid leukemia. A study by the French ALFA group

Abstract: Assessment of minimal residual disease has emerged as a powerful prognostic factor in acute myeloid leukemia. In this study, we investigated the potential of IDH1/2 mutations as targets for minimal residual disease assessment in acute myeloid leukemia, since these mutations collectively occur in 15–20% of cases of acute myeloid leukemia and now represent druggable targets. We employed droplet digital polymerase chain reaction assays to quantify IDH1R132, IDH2R140, and IDH2R172 mutations on genomic DNA in 322 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
(43 reference statements)
5
29
0
Order By: Relevance
“…Ferret et al reported the study of 103 AML patients with IDH mutations enrolled on Acute Leukemia French Association (ALFA)-0701 and 0702 clinical trials. The mutant allele fraction (VAF) was 42.3% (range 8–49.9%) in bone marrow at diagnosis and below the detection limit of 0.2% (range <0.2-39.3%) in complete remission after induction therapy; in univariate analysis a IDH1/IDH2 VAF < 0.2% in bone marrow after induction therapy was a predictor of longer disease-free survival [ 137 ]. In 7% of patients, IDH1/IDH2 mutations persisted at high levels in complete remission, suggesting the presence in these patients of IDH mutations at the level of the preleukemic stem cell pool; five out of these seven patients relapsed or progressed to MDS [ 137 ].…”
Section: Are Idh Mutations a Suitable Marker For Minimal Residualmentioning
confidence: 99%
“…Ferret et al reported the study of 103 AML patients with IDH mutations enrolled on Acute Leukemia French Association (ALFA)-0701 and 0702 clinical trials. The mutant allele fraction (VAF) was 42.3% (range 8–49.9%) in bone marrow at diagnosis and below the detection limit of 0.2% (range <0.2-39.3%) in complete remission after induction therapy; in univariate analysis a IDH1/IDH2 VAF < 0.2% in bone marrow after induction therapy was a predictor of longer disease-free survival [ 137 ]. In 7% of patients, IDH1/IDH2 mutations persisted at high levels in complete remission, suggesting the presence in these patients of IDH mutations at the level of the preleukemic stem cell pool; five out of these seven patients relapsed or progressed to MDS [ 137 ].…”
Section: Are Idh Mutations a Suitable Marker For Minimal Residualmentioning
confidence: 99%
“…They showed that DNMT3A and IDH alterations may persist in patients in remission at long-term, confirming that these mutations are not disease-specific and may be eliminated by allo-SCT only. Although the prognostic value of IDH mutations is still unclear (72), Ferret et al (73) demonstrated that ddPCR monitoring of IDH mutations after allo-SCT, could help to early identify disease persistence and anticipate hematologic relapse. These data have been confirmed by Winters et al who demonstrated the utility of ddPCR for post-SCT MRD monitoring (74).…”
Section: Digital Droplet Pcr (Ddpcr)mentioning
confidence: 99%
“…In most studies, IDH mutations were found to be heterozygous, resulting in a gain of function phenotype, occurring primarily in three arginine residues critical for isocitrate binding-the R132 codon in IDH1 and the R140 and R172 in IDH2 [44,45]. It has been proposed that the mutant allele burden of IDH can be a biomarker of response to treatment in AML patients [46]. Nonetheless, there is still some controversy about the prognostic value of IDH mutations in AML.…”
Section: Metabolic Reprogramming In Acute Myeloid Leukemiamentioning
confidence: 99%